Amazing lizards! - Robinson, Fay.; Zallinger, Jean (New York : Scholastic, 1999)
Rhyming text and illustrations introduce the colorful world of lizards. Includes a reference section providing more information about the lizards mentioned in the text.
"Kindergarten-Grade 2"--Cover. Paperback
"Cartwheel books."
460
460
Keywords: Lizards -- Juvenile literature; Lizards